ROLE OF PREBIOTICS IN TREATMENT OF FUNCTIONAL CONSTIPATIONS IN CHILDREN - E.V. Komarova; O.S. Gundobina (Union of pediatricians of Russia, 2009)
The article is devoted to the functional disorders of the large bowel motility among children. The authors examine the reasons for the given pathology and opportunities for the lactulose application as a prebiotic within the comprehensive therapy.Key words: constipation, treatment, prebiotics, children.